Distance dimensions and their impact on business cooperation in a tourist destination - Czernek-Marszałek, Katarzyna (Wymiary dystansu i ich wpływ na współpracę gospodarczą w destynacji turystycznej, 2019)
Interorganizational cooperation depends on many factors including the similarity and differences between the partners in terms of e.g. organizational culture, knowledge, resources, or in relation to geographical location to each other. These differences can be analyzed by using the concept of distance which occurs in various dimensions. The aim of the paper is to identify distance dimensions and to indicate how they affect business cooperation in a tourist destination. To achieve this aim, the research on economic cooperation was used, involving semi-structured interviewees with tourist entrepreneurs operating in different Polish municipalities. Research showed that all types of distance dimensions (cognitive, communicative, organizational, functional, social, cultural and geographical) are important for tourism cooperation, although in relation to the processes related to a given territory (e.g. tourism development) the role of some of them, such as social distance or geographical, is crucial
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 7, s. 217-229
Keywords: distance; proximity; distance dimension; cooperation; tourist region; dystans; bliskość; wymiar dystansu; współpraca; region turystyczny